2022
DOI: 10.3952/physics.v62i2.4744
|View full text |Cite
|
Sign up to set email alerts
|

17O NMR and DFT study of hydrogen bonding: Proton sharing and incipient transfer

Abstract: O NMR spectra of pyridine N-oxide (PyO) complexes with the acids – acetic (AA), cyanoacetic (CyA), propiolic (PA), trichloroacetic (TCA), trifluoroacetic (TFA), hydrochloric (HCl) and methanesulfonic (MSA) – as well as some related molecules with intramolecular H-bonds (4-substituted picolinic acid N-oxides) were studied in an acetonitrile (ACN) solution. In order to evaluate the effect of proton positioning along the O–H…O bond on the measured chemical shifts the full geometry optimization was carried out, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…The series of complexes in that study 37 was found to be approximately ordered by increasing the values of their acid dissociation constants (pKa) in parallel with the 13 C NMR chemical shifts of ring carbons. Indeed, the whole series of compounds could be subdivided into two parts, namely, the neutral B … H-A bonds with r(O-H)/R (O … O) < 0.5 and the ionic pairs BH + … A with r(O-H)/ R(O … O) > 0.5, resulting from the proton transfer process.…”
Section: Systems With Hydrogen Bondingmentioning
confidence: 87%
See 4 more Smart Citations
“…The series of complexes in that study 37 was found to be approximately ordered by increasing the values of their acid dissociation constants (pKa) in parallel with the 13 C NMR chemical shifts of ring carbons. Indeed, the whole series of compounds could be subdivided into two parts, namely, the neutral B … H-A bonds with r(O-H)/R (O … O) < 0.5 and the ionic pairs BH + … A with r(O-H)/ R(O … O) > 0.5, resulting from the proton transfer process.…”
Section: Systems With Hydrogen Bondingmentioning
confidence: 87%
“…In the most recent publication in this field, Balevičius and coauthors 37 reported the 17 O NMR spectra of pyridine N-oxide (PyO) complexes with a number of mainly organic acids, namely, acetic (AA), cyanoacetic (CyA), F I G U R E 6 Experimental (upper traces) and simulated (lower traces) 17 O nuclear magnetic resonance (NMR) spectra (21.14 T) of glycerol at different temperatures. The total line shapes are shown in red.…”
Section: Systems With Hydrogen Bondingmentioning
confidence: 99%
See 3 more Smart Citations